2020
DOI: 10.1109/access.2020.3007502
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Networked Wireless Sensor Data Collection for Computational Intelligence Techniques: Issues, Challenges, and Approaches

Abstract: Underwater wireless sensor networks (UWSNs) is emerging as an advance terminology for monitoring and controlling the underwater aquatic life. This technology determines the undiscovered resources present in the water through computational intelligence (CI) techniques. CI here pertains to the capability of a system to acquire a specific task from data or experimental surveillance below the water. In today's time data is considered as the identity for everything that exists in nature, whether that data is relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…The authors of [27] presented different methodologies that allow the underwater detection of coronavirus with the use of various sensors available in the different types of devices. However, they reported reliable results with the proposed system.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of [27] presented different methodologies that allow the underwater detection of coronavirus with the use of various sensors available in the different types of devices. However, they reported reliable results with the proposed system.…”
Section: Resultsmentioning
confidence: 99%
“…Also, packets are transmitted on the basis of channel conditions and link quality by which reliability of the network is increased but the energy tax is compromised. In [2], authors have addressed different issues and suggested various techniques for efficient data collection in a harsh underwater WSNs. According to them, computational intelligence technique seems a prominent solution for efficient data collection from underwater environments.…”
Section: A Reliable Data Transfer Techniquesmentioning
confidence: 99%
“…A cube has six sides and eight vertices 2. Cube can also be referred to as a cluster and vice versa hereinafter.VOLUME 4, 2016…”
mentioning
confidence: 99%
“…11 The initial deployments of WSNs assume that the sensors and base station/sink are static, and researchers are naturally led to the other paradigms of WSNs where sensors and base station are mobile. 12 Such mobile WSNs are expected to find many applications. 13 The simple energy constraints of various densely deployed sensor nodes need a suite of network protocols to set up various network control and management functions such as synchronization, node localization, 14 and network security.…”
Section: Literature Surveymentioning
confidence: 99%
“…The growing amount of IoT devices and the essentials of huge data handling would multiply the number of packets, where this issue can be a serious problem to the legacy network architecture 11 . The initial deployments of WSNs assume that the sensors and base station/sink are static, and researchers are naturally led to the other paradigms of WSNs where sensors and base station are mobile 12 . Such mobile WSNs are expected to find many applications 13 .…”
Section: Literature Surveymentioning
confidence: 99%